Global Handicraft Index: A Pioneering Approach and developing strategies for promotion, competition, and artisan in the world - Uma Shankar Yadav; ravindra tripathi; nikhil yadav (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
The purpose of this paper is to give a separate index for the development of handicraft products developing better completion in handicraft industries, conserving the heritage of all countries handmade tradition, the skill of artisans, making them entrepreneurship to artisans Among them, we know that whole world is facing a big problem of plastic glass and other population and climate is also affecting due to environmental pollution in the world so if all want to maintain their life and living patter better and sustainable then they should have to make the product for their utility that is sustainable and utility decorative and that will have to give local job and enhancing the local talent of the artisan and rural, tribal people special women. We know that all are worker but want to be entrepreneur and earn their mount and increase the GDP of their country and in last want to be happy in the world so the objetive to the paper is to develop and innovation and suggest first global handicraft index like as global innovation index global happiness index , global hanger index , global environments risk assessment index and other index that have help the world each country for developing and giving better competition between the other sector ,and other sector so in case of handicraft sector that artisans , and worker ground completion’s , better development , capacity building of the artisan women empowerment in handicraft sector and in last socioeconomic welfare of artisan and over global development the reviving of handicraft industry in the world that is facing huge problem in comparison of machine made product in current scenario and to conserve our local talent , our heritage product , our tradition and ancient skill and monument and sustainability to priodht and eco-friendly living pattern of the people in whole world such ancient crafts as pottery, weaving mats, baskets, making painted chests, tambour embroidery, etc. And in many regions of Azerbaijan these ancient handicrafts, not only do not decline but continue to flourish and develop for the joy of all connoisseurs of folk art. This is helping in providing 11 parameters and 20 indicators on which the proposed handicraft index will be prepared at the global level. so there is a need for initiative for researchers that want to work in the sector of the handicraft industry and to want to give the new horizon at the front of other machine-made products that are harmful and costly non-eco-friendly and that is trading and increasing jobless growth so this handicraft index will help to at artisan increasing the employment, income decreasing the jobless growth converting the gig worker and creating local talent and making it as the global label.